Village Government Strategies in Managing the Village Library as a Facility for Providing Information to the Community in Biroro Village - Sitti Fatimah (Tinta Emas Institute, 2023)
The purpose of this research is to investigate and analyze the strategies employed by the Village Government in managing the Village Library as a means of providing information services to the community in Biroro Village. This research utilizes a qualitative descriptive research method and incorporates both primary and secondary data sources. Data is collected through observation, interviews, and documentation, involving various informants such as the Head of Biroro Village, the Village Secretary, the Village Finance Officer, the Village Consultative Body (BPD), the Village Library Manager, and the residents of Biroro Village. Data analysis encompasses data collection, data reduction, data presentation, and drawing conclusions. The research findings indicate that the management of the village library in Biroro is not fully compliant with the regulations set by the Local Government. Despite the Village Government's planning of programs, their implementation faces significant obstacles. The Village Government has allocated a budget and established a dedicated office for the library; however, the effectiveness of these programs' implementation is still lacking. Moreover, the adherence to the National Standards for Village Library Management has not been optimal. Supervision tends to focus more on execution rather than ensuring compliance with the stipulated regulations. Although the library management's reporting is reasonably good, budget constraints hinder the acquisition of collections and the provision of library services. Hence, there is a need for improvements in the management of the village library to meet the community's information needs and support better human resource development.